HUBUNGAN KEPRIBADIAN QUR’ANI DENGAN RESELIENSI AKADEMIK PADA MAHASISWA AKHIR DI BUKITTINGGI - Hendri, Mutiara; Aprillia, Ririn; Mutiara Desky, Elsa; Amillusholihati, Gina (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
This research is a quantitative study which aims to find out whether there is a relationship between quranic personality and academic resilience in the final students of Bukittinggi class of 2020 who are writing their theses. In this study, the sample was all Bukittinggi students with a total research sample of 100 students. The measuring instruments used in this research are the academic resilience scale and the koranic personality scale. The scale was processed using statistics with the help of a statistical computer program with the help of a computer program in the form of statistical package for social science (SPSS) version 29.0 for windows. In this research, the data analysis used is the person product moment statistical test. Product moment correlation is used to see the relationship between Al-Quranic personality and academic resilience in Bukittinggi students. The research results show that there is no significant correlation between the quranic personality variables and academic resilience. It is known that the calculated r value (person correlations) for the Quranic personality relationship (X) is -0.059 > r table 0.195. So it can be concluded that there is no relationship or correlation between the quranic personality variable and academic resilience.